Factors influencing second language learning based on the research of Lightbown and Spada - Qiao, Chuandai (Frontiers in Psychology, 2024)
Deep insights into the factors influencing second language learners can positively impact learners' self-intervention and guide language teachers in selecting appropriate teaching materials and strategies. Drawing from Lightbown & Spada's framework encompassing motivation, aptitude, personality, intelligence, and learner preferences, this paper examines the relationship between individual learners' characteristics and second language learning effects across five aspects by dialectically considering the research methods suitable for different learner variables. By incorporating recent research and offering practical implications, this paper has the potential to contribute valuable insights to both researchers and practitioners in the field of language education.